Efeito fotodinâmico da curcumina sobre a proliferação celular em áreas com periodontite induzida em ratos - Bueno, Tamara Seraphim [UNESP] (2015)
Periodontal disease is a chronic inflammatory condition initiated by an immune response to biofilm microorganisms. The aim of this study was to evaluate by Immunohistochemistry through the nuclear antigen immunostaining of cell proliferation (PCNA), the influence of curcumin as a photosensitizing agent associated with LED irradiation in APDT (antimicrobial photodynamic therapy) for the treatment of periodontitis experimentally induced in rats. Ninety-six animals were subjected to the induction of periodontitis by the installation of a cotton thread around the first molars, which was maintained for 7 days. The animals were randomly divided into 4 groups containing 24 animals each, which were given the following treatments: G1 (n = 24) - represented by animals which suffered no local treatment; G2 (n = 24) - irrigation solution of curcumin (40μM); G3 (n = 24) - irradiation with LED (Light Emitting diode); G4 (n = 24) - Curcumin irrigation solution (40μM) followed by irradiation with LED. Local treatments were carried out 7 days after the induction of periodontitis. The LED light, which was used in this study for the achievement of aPDT is a semiconductor emitter of indium gallium Nitride (InGaN), with a wavelength of 465 to 485nm and irradiance of 600mW / cm². LED irradiation was performed for 60 seconds in the vestibular face of lower left first molars. Treatment in G4 with LED was performed after 60 seconds of the irrigation with curcumin photosensitizer. The animals, in number of 8 for each group / time were euthanized at intervals of 7, 15 and 30 days after treatment. After euthanasia, specimens underwent immunohistochemical evaluation by immunostaining of PCNA. Data were subjected to statistical analysis with 5% significance level. The animals of G1 presented higher number of positive PCNA cells at 15 days, compared...